PERENCANAAN KOMUNIKASI PROGRAM PASAR AMAN DARI BAHAN BERBAHAYA OLEH BALAI BESAR PENGAWAS OBAT DAN MAKANAN (BBPOM) DI PEKANBARU (STUDI PADA PASAR LIMA PULUH) - Rika Juliana; Welly Wirman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
Control of the abuse of hazardous substances in food should be carried out in all existing traditional markets. However, there needs to be a priority scale so that control can be carried out in stages. Market identification needs to be done to select target markets where these target markets generally meet the criteria for a healthy market in accordance with Decree of the Minister of Health No. 519/Menkes/SK/VI/2008 concerning Guidelines for Organizing Healthy Markets. Communication planning carried out by the Center for Drug and Food Control (BBPOM) in Pekanbaru is to carry out a safe market program for hazardous materials and then determine who the target audience is, channels and media selection, message design, and monitoring and evaluation selection. This study aims to determine the communication planning for the safe market program for hazardous materials by the BBPOM Drug and Food Supervisory Agency in Pekanbaru 2020. This study uses a qualitative method with a descriptive approach. There are ten informants taken through the techniquepurvosive. Types and sources of data were obtained through primary data and secondary data. Data collection was carried out by interviews, observation and documentation. Data analysis techniques by reducing data, presenting data and drawing conclusions. Furthermore, checking the validity of the data was carried out by extending participation and triangulation. The results of this study indicate that the communication planning used by the Food and Drug Supervisory Agency (BBPOM) in Pekanbaru in carrying out the safe market program for hazardous materials is quite effective using the Assifi and Franch communication planning model where the Food and Drug Supervisory Agency determines from the stage the target audience is the market manager, the target fifty market traders, the target fifty market consumers, the goal of the safe market program from hazardous materials is to make the fifty market a market free of hazardous materials. Second, in terms of channel selection and media, BBPOM in Pekanbaru uses interpersonal communication channels, group communication, public communication and small format media where this media selection is felt to be very effective in conveying the objectives of the safe market program for hazardous materials. Third, the messages conveyed in the safe market program for hazardous materials consist of verbal and nonverbal messages while the nature of the messages consists of informative, persuasive, and educative where the message invites the target to keep the market protected from hazardous materials. Fourth, in terms of monitoring and evaluation, there are two stages in determining the success of the program.